Sharing Knowledge with the Community on the Utilization of IT-Based Pyrolysis Technology for Independent Waste Management - Muhammad Amanulloh Mz (NJCOM: Community Service Journal, 2025)
The waste problem continues to increase along with population growth and consumption. Effective waste management is crucial to maintain environmental cleanliness and public health. This community service article aims to transfer knowledge to the community about the use of IT-based pyrolysis technology for independent waste management. The community will be introduced to the concept of pyrolysis, which is the process of decomposing organic waste into valuable products, such as bio-oil, bio-char, and gas. In addition, the community is expected to be trained to operate and maintain an IT-based pyrolysis system, which allows efficient monitoring and control of the process. Through this article, the public can understand and adopt IT-based pyrolysis technology to manage household waste independently. This will reduce the volume of waste disposed of in landfills, as well as produce products that can be reused. Thus, the community can contribute to the creation of a clean, healthy, and sustainable environment.